Caracterización del virus del mosaico amarillo dorado del frijol en Cuba - Echemendia Gómez, A.L.; Ramos Gonzalez, PL; Villarreal, N.; Martínez, A.K.; González Arias, G.A.; Morales, Francisco José (2010)
The common bean (Phaseolus vulgaris L.) has its origin in America, where it is consider as one of the basic foods. In Cuba, the emergence of bean golden mosaic was associated with high populations of Bemisia tabaci in common bean plantings in the 1970s. Persistent infections and crop losses caused by the virus have been reported. With these considerations, the objectives of this work were dedicated to the biological, serological and molecular characterization of the Cuban isolates of BGYMV. Biological, inmunoenzimatic and molecular methods were used for the characterization. Characteristic yellowing symptoms were reproduced using manual inoculation and in ELISA test, Cuban isolates of BGYMV reacted efficiently with 3F7 monoclonal antibody but not with 2G5. Fragment length polymorphism analysis of 1.2 and 1.4 kb cloned fragments revealed similar patterns for isolates from ten provinces. However, they differ from other isolates of the region. The nucleotide and amino acid sequence from Cuban isolates shared the best percentage of identity with the Florida isolate. The iterative sequence ATGGAG was identified in the common region of the Cuban BGYMV isolates. Furthermore, the biological, serological and molecular characterization showed that isolate of BGYMV is a member of the Mesoamerican BGYMV group.